"Enzymogenesis": classical liver alcohol dehydrogenase origin from the glutathione-dependent formaldehyde dehydrogenase line. - Danielsson, O (1992)
Analysis of the activity and structure of lower vertebrate alcohol dehydrogenases reveals that relationships between the classical liver and yeast enzymes need not be continuous. Both the ethanol activity of class I-type alcohol dehydrogenase (alcohol:NAD+ oxidoreductase, EC 1.1.1.1) and the glutathione-dependent formaldehyde activity of the class III-type enzyme [formaldehyde:NAD+ oxidoreductase (glutathione-formylating), EC 1.2.1.1] are present in liver down to at least the stage of bony fishes (cod liver: ethanol activity, 3.4 units/mg of protein in one enzyme; formaldehyde activity, 4.5 units/mg in the major form of another enzyme). Structural analysis of the latter protein reveals it to be a typical class III enzyme, with limited variation from the mammalian form and therefore with stable activity and structure throughout much of the vertebrate lineage. In contrast, the classical alcohol dehydrogenase (the class I enzyme) appears to be the emerging form, first in activity and later also in structure. The class I activity is present already in the piscine line, whereas the overall structural-type enzyme is not observed until amphibians and still more recent vertebrates. Consequently, the class I/III duplicatory origin appears to have arisen from a functional class III form, not a class I form. Therefore, ethanol dehydrogenases from organisms existing before this duplication have origins separate from those leading to the "classical" liver alcohol dehydrogenases. The latter now often occur in isozyme forms from further gene duplications and have a high rate of evolutionary change. The pattern is, however, not simple and we presently find in cod the first evidence for isozymes also within a class III alcohol dehydrogenase. Overall, the results indicate that both of these classes of vertebrate alcohol dehydrogenase are important and suggest a protective metabolic function for the whole enzyme system.